The Description Of National Commitment Value Among Students of STAKPN Sentani Papua - Natalia, Arie Rissing; Malatuny, Yacob Godlif; Kartika, Mesri (Sekolah Tinggi Teologi Kadesi Yogyakarta, 2024)
Papua is one of Indonesia's regions prone to disintegration because some organizations continue to speak of distrust of the central government. Those organizations are called OPM (Free Papua Movement). This study aims to assess the internalization of the values of national commitment through the subject of Christian Education in Compound Society at STAKPN Sentani Papua students. The results of this research can contribute to the government's making policies for peace and integration in Papua. The research includes descriptive quantitative research. Data was collected by questionnaire and analyzed by crosstabs analysis. The results of the study found that the internalization of Christian Education in Compound Society to the value of the commitment to the unity of the Republic of Indonesia was obtained significantly, but for the commitment to love the homeland, willing to sacrifice, maintain the Republic of Indonesia and the unity of the Republic of Indonesia was not significant. The results of this study recommend that students continue to value the commitment to the unity of the Republic of Indonesia because, after all, Papua remains an inseparable part of the Republic of Indonesia. Overall, we found that STAKPN Sentani students, through the subject of Christian Education in a compound society, can have an excellent national commitment value.